A Model of Trading in the Art Market - Lovo, Stefano; Spaenjers, Christophe (American Economic Review, 2018)
We present an infinite-horizon model of endogenous trading in the art auction market. Agents make purchase and sale decisions based on the relative magnitude of their private use value in each period. Our model generates endogenous cross-sectional and time-series patterns in investment outcomes. Average returns and buy-in probabilities are negatively correlated with the time between purchase and resale (attempt). Idiosyncratic risk does not converge to zero as the holding period shrinks. Prices and auction volume increase during expansions. Our model finds empirical support in auction data and has implications for selection biases in observed prices and transaction-based price indexes. (JEL C43, D44, E32, Z11)